Neural circuits in the mouse retina support color vision in the upper visual field - Klaudia P. Szatko (Nature Portfolio, 2020)
Mice are able to discriminate colors, at least in the upper visual field. Here, the authors provide a comprehensive characterization of retinal circuits underlying this behavior.